IN VITRO ANTIMICROBIAL ACTIVITY OF POLYHERBAL OINTMENT AGAINST HUMAN PATHOGENIC BACTERIA - Mahajan Sachin.M.; Bhandari Harshal. R. (Journal of Population Therapeutics and Clinical Pharmacology, 2022)
The aim of the study was assess the antimicrobial effect of some medicinal plants and its formulation against Escherichia coli, Candida albicans, Aspergillus niger. Medicinal plants are the important source of potentially useful structures for the development of novel chemotherapeutic agents. Historically, plants have provided a source of the development for novel drugs and plant derived drugs which have made large contributions to human health and wellbeing. The hydro-alcoholic extract of selected medicinal plant show presence of major phyto-constituent such as alkaloids, glycosides, steroids, flavonoids, tannins etc. The antimicrobial activities of selected plants extracts were evaluated using the disk diffusion method .In the present study, polyherbal formulation was screened against microorganism at the concentration of 100 /ml with reference standard DERMIKEM OC Cream. At above concentration there is antibacterial activity found in PHF A and B They not show antifungal activity.